2020
DOI: 10.3390/educsci10020039
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Indonesian Science Teachers’ Experience and Perceptions toward Socio-Scientific Issues-Based Science Education

Abstract: This survey explored Indonesian science teachers’ experience and perceptions toward science teaching that is based on socio-scientific issues (SSIs). The participants were asked whether or not they already used corresponding practices in their own teaching and whether they experienced any challenges in implementing SSI-based pedagogies. Further focal points were the teachers’ views on student competencies that can be fostered through SSI-based education, the connection of SSI-based pedagogies with students’ ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 39 publications
(45 reference statements)
9
49
0
4
Order By: Relevance
“…From the findings, there is a conflict or gap between the implementation of SSI that focus on students and the achievement of learning objectives [22]. Research with the same results also occurred in Indonesia by Nida et al that revealed that although many teachers consider SSI-based learning as a promising strategy, several obstacles need to be addressed immediately [21].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…From the findings, there is a conflict or gap between the implementation of SSI that focus on students and the achievement of learning objectives [22]. Research with the same results also occurred in Indonesia by Nida et al that revealed that although many teachers consider SSI-based learning as a promising strategy, several obstacles need to be addressed immediately [21].…”
Section: Introductionmentioning
confidence: 63%
“…In Indonesia itself, SSI-based approaches do not appear to have been widely developed and have had only limited influence on curriculum reform in science education [21]. Research by Nida et al [21] revealed, although the teachers viewed SSI-based learning positively and saw its potential for character building; the participants did not show a high level of implementation of SSI-based learning in their class. It is suggested that teachers should be given more resources and provided comprehensive support to overcome the difficulties faced in implementing SSIbased learning [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations